THE RELATIONSHIP BETWEEN OBSTRUCTIVE SLEEP APNEA AND CRANIOFACIAL ANOMALIES IN ADULT PATIENTS - N Tkadlecová; P Černochová (Czech Dental Chamber, 2021)
Introduction: Obstructive sleep apnoea (OSA) is considered to be a serious condition associated with daytime sleepiness which leads to cognitive impairment, hypertension, cardiovascular diseases and diabetes mellitus. OSA is a sleep disorder with multifactorial etiology characterised by recurrent episodes of partial or complete obstruction of upper airways during sleep, leading to a decrease in blood oxygen saturation level to 70%.Presentation: The prevalence of OSA is high in adult patients in developed countries. Orthodontists often look after patients with OSA, whose craniofacial and dental anomalies, biotype of the facial skeleton and specific pathologies of the cervical spine are associated with obstruction of upper and lower airways. Craniofacial and dental anomalies usually involve skeletal class II., which is commonly combined with Angle class II. and increased overjet, mandibular posteriorotation, shorter mandibular length, increased mandibular plane angle in combination with anterior open bite, mandibular retrognathia, bimaxillary retrusion, narrow and high hard palate presenting as lateral crossbite. Other important signs include thicker and elongated soft palate, enlarged tongue and inferior position of the hyoid bone. Hypertrophy of the adenoid, palatine and lingual tonsils is also an important anatomic factor in etiology of OSA. Imaging methods are frequently used to diagnose these anomalies: orthopantomograms, lateral cephalograms, computed tomography and magnetic resonance imaging.The aim of the article is to review craniofacial structures which contribute to developing OSA and to compare eight European studies proving the relationship between OSA and these anomalies.Conclusion: Interdisciplinary cooperation among an orthodontist, otorhinolaryngologist, neurologist and internist is very important for appropriate treatment of OSA. The orthodontic examination should be performed in every patient with diagnosis OSA due to high frequency of the craniofacial abnormalities that are usually missed.